UNDERWATER TECHNOLOGY ESSENTIAL TO SAFEGUARD SOVEREIGNTY OF THE NATION’S WATERS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
NIBONG TEBAL, 10 December 2015 The tragedy of the missing airliner MH370 has shown that there are still deep sea mysteries which have yet to be solved by man, due to the current inadequate technology and systems which demand necessary enhancements.